Concurrence of Meningomyelocele and Salt-Wasting Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency - Heves Kırmızıbekmez; Rahime Gül Yesiltepe Mutlu; Serdar Moralıoğlu; Ahmet Tellioğlu; Ayşenur Cerrah Celayir (Case Reports in Pediatrics)
Congenital adrenal hyperplasia (CAH) is a group of inherited defects of cortisol biosynthesis. A case of classical CAH due to 21-hydroxylase deficiency (21-OHD) with early onset of salt waste and concurrence of meningomyelocele (MMC) was presented here. The management of salt-wasting crisis which is complicated by a postrenal dysfunction due to neurogenic bladder was described. Possible reasons of growth retardation in the one-year follow-up period were discussed. A significant regression of the phallus with proper medical treatment was also mentioned.